Frequent Epigenetic Silencing of the Folate-Metabolising Gene Cystathionine-Beta-Synthase in Gastrointestinal Cancer - Zhao, Hong; Li, Qinshan; Wang, Jian; Su, Xianwei; Ng, Ka Man; Qiu, Tian; Shan, Ling; Ling, Yun; Wang, Linfang; Cai, Jianqiang; Ying, Jianming (PLOS ONE, 2012)
Background Both gastric and colorectal cancers (CRC) are the most frequently occurring malignancies worldwide with the overall survival of these patients remains unsatisfied. Identification of tumor suppressor genes (TSG) silenced by promoter CpG methylation uncovers mechanisms of tumorigenesis and identifies new epigenetic biomarkers for early cancer detection and prognosis assessment. Cystathionine-beta-synthase (CBS) functions in the folate metabolism pathway, which is intricately linked to methylation of genomic DNA. Dysregulation of DNA methylation contributes substantially to cancer development. Methodology/Principal Findings To identify potential TSGs silenced by aberrant promoter methylation in CRC, we analyzed tumor and adjacent tissues from CRC cases using the Illumina Human Methylation45 BeadChip. We identified hypermethylation of the CBS gene in CRC samples, compared to adjacent tissues. Methylation and decreased mRNA expression of CBS were detected in most CRC cell lines by methylation-specific PCR and semiquantitative RT-PCR, as well as in gastric cancer. Treatment with 5-aza-2'-deoxycytidine and/or trichostatin A reversed methylation and restored CBS mRNA expression indicating a direct effect. Aberrant methylation was further detected in 31% of primary CRCs (29 of 96) and 55% of gastric tumors (11 of 20). In contrast, methylation was seldom found in normal tissues adjacent to the tumor. CBS methylation was associated with KRAS mutations in primary CRCs (P = 0.04, by χ2-test). However, no association was found between CBS methylation or KRAS mutations with cancer relapse/metastasis in Stage II CRC patients. Conclusion A novel finding from this study is that the folate metabolism enzyme CBS mRNA levels are frequently downregulated through CpG methylation of the CBS gene in gastric cancer and CRC, suggesting that CBS functions as a tumor suppressor gene. These findings warrant further study of CBS as an epigenetic biomarker for molecular diagnosis of gastrointestinal cancers.